(untitled) (Journal of Pharma Insights and Research, 2025)
A 27-year-old postpartum female presented to the emergency department with grade IV orthopnea, bilateral lower limb edema, and a history of severe hemorrhage during cesarean delivery. The patient had pre-existing type 3C diabetes mellitus (Fibro calculous Pancreatic Diabetes), asthma, and hypothyroidism. Laboratory investigations revealed profound anemia (Hb 6.6 g/dL), thrombocytopenia (91 × 10⁹/L), acute kidney injury (creatinine 2.43 mg/dL), and marked endocrine abnormalities. Hormonal evaluation demonstrated significantly reduced free T3 (0.89 ng/dl) with concurrent signs of hypopituitarism. ECG showed extreme tachycardia with low-voltage limb leads. The diagnosis of Sheehan’s syndrome was established based on the clinical presentation, postpartum hemorrhage history, and hormonal profile. The patient developed acute decompensated heart failure with pleural effusion, necessitating immediate medical intervention. Management included diuretic therapy, hormone replacement, and cardiovascular support. The patient showed gradual improvement with stabilization of vital parameters and reduction in peripheral edema by day 5 of hospitalization. Blood pressure normalized to 130/90 mmHg, and renal function showed progressive improvement. The case highlights the importance of early recognition of Sheehan’s syndrome in postpartum women, particularly when presenting with multisystem involvement. Early treatment using hormone replacement therapy along with management of associated complications remains crucial for favorable outcomes